Parenthetic Сonstructions the Texts of Modern Ukrainian Economic Discourse - Ковальська, Наталя Аркадіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article investigates the parenthetic constructions and their value in modern Ukrainian economic discourse. The nature parenteticheskih structures and the principle of differentiation and the plug inserted components in modern linguistics. Presented classification by type of imbedded in sentence meaning. Structural parameters and pragmatic function inserts are characterised. Analysis of the functioning parenthetic constructions in texts economic discourse on the material articles of modern Ukrainian magazine «The Economist».